Transformational principal leadership and teacher performance as predictors of primary education quality: a multiple regression study - Eko Rudiyanto; Edi Harapan; Syaiful Eddy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examined the individual and simultaneous contributions of principals’ transformational leadership and teacher performance in predicting educational quality in public elementary schools. A quantitative cross-sectional correlational design was employed. The population consisted of 88 teachers from seven public elementary schools in Muara Telang District, Banyuasin Regency. A sample of 72 teachers was selected using proportional random sampling based on the Slovin formula with a 5% margin of error. Data were collected using Likert-scale questionnaires. All 30 transformational-leadership items and all 30 teacher-performance items were valid, whereas 29 of 30 educational-quality items were valid. Each scale demonstrated high internal consistency (Cronbach’s alpha = 0.80). Data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression. Transformational leadership significantly predicted educational quality and explained 26.2% of its variance (R = 0.512; R² = 0.262; t = 4.988; p < 0.001). Teacher performance also significantly predicted educational quality and explained 21.7% of its variance (R = 0.466; R² = 0.217; t = 4.407; p < 0.001). Simultaneously, both predictors explained 34.0% of the variance in educational quality (R = 0.583; R² = 0.340; adjusted R² = 0.320; F(2, 69) = 17.737; p < 0.001). The overall model demonstrated a substantial effect size (Cohen’s f² = 0.515) and statistical power exceeding 0.99. The findings indicate that transformational principal leadership and teacher performance are complementary predictors of educational quality. Because the design was cross-sectional and correlational, the results should be interpreted as predictive associations rather than definitive causal relationships.